Interactive digital storytelling using story graph approach / Nur Azima Alya Narawi - Narawi, Nur Azima Alya (2021)
The flow of the storyline should be structured well and organized for it to be understandable and complete. Digital storytelling is becoming more attractive these days, as all the information and entertainment progresses into digital devices. Digital storytelling offers more interactivity by creating an interactive storyline due to the problem statement is having a challenge in making a story structure that works with interactive structure. Besides, there are no computer techniques that support interactive patterns. Therefore, the creation of a new story structure named Interactive Story Graph Structure (ISGS) is a story structure model that incorporates the three interactive features which are interactivity, iteration, and multi-option. This research study demonstrates the storyline using the ISGS that consists of new symbols that are adapted to the design from existing symbols. The ISGS is created by applying the symbols and allows customize the interactive storyline flow based on the guidelines. The symbols are used to make options, repetitive flow, and revert process within the storyline. The digital storytelling prototype has been implemented by showing the storyline flow using the ISGS. The user acceptance test has been assessed by 10 expert reviewers. The overall result shows that 91.3% able to accept the new story structure as a process to interpret the interactive storyline before generates into digital storytelling based on descriptive analysis and the frequency values in bar chart using SPSS. Hopefully, the ISGS able to improve the development of interactive and digital storytelling applications.